A longitudinal study of work‐related psychosocial factors and injuries: Implications for the aging United States workforce. Issue 3 (23rd January 2019) - Baidwan, Navneet K.; Gerberich, Susan G.; Kim, Hyun; Ryan, Andrew; Church, Timothy; Capistrant, Benjamin
Abstract : Introduction: This study aimed to identify psychosocial work factors that may individually or, in combination, influence injury outcomes among aging United States (U.S.) workers. Methods: Data from the U.S. Health and Retirement Study (HRS) of 3305 working adults, aged 50 years and above, were used to identify associations between work‐related psychosocial factors and injury incidence from 2006 to 2014, using adjusted incidence rate ratios. Results: Employees perceiving their work as high in psychological and physical demands/efforts, low in support, and rewards, compared to those in workplaces with low demands, high support, and high rewards, had a risk of injury two times greater. Males, compared with females, had a greater risk for injuries when interactions among several psychosocial work‐related factors were modeled. Conclusions: The fact that important gender‐based differences emerged when interactions among the psychosocial factors and injury were modeled, suggests opportunities for further research and potential interventions to enhance the working environment.